Duration of meconium passage in preterm and term infants. Issue 5 (19th February 2008) - Bekkali, N; Hamers, S L; Schipperus, M R; Reitsma, J B; Valerio, P G; Van Toledo, L; Benninga, M A
Abstract : Background: First passage of stool after birth, meconium, is delayed in preterm infants compared to term infants. The difference in duration of meconium passage until transition to normal stools has however never been assessed in preterm and term infants. Hypothesis: Preterm infants have prolonged duration of passage of meconium (PoM) compared to term infants. Methods: Between August and November 2006, all infants born in an academic and non-academic hospital with gestational age (GA) 25–42 weeks and without metabolical, congenital diseases or gastrointestinal disorders, were included. Infants were divided into four groups: (A) GA ⩽30 weeks; (B) GA between 31 and 34 weeks; (C) GA between 35 and 36 weeks; (D) GA ⩾ 37 weeks (term born). Results: A total of 198 infants (102 males); 32, 62, 33 and 71 infants in groups A, B, C and D, respectively, were included. With decreasing gestation a trend was found for delayed first PoM (p<0.001). Compared to term infants 79% (56/71), less preterm infants passed their first stool within 24 h after birth — group A: 44% (14/32); group B: 68% (42/62); and group C: 73% (24/33). With decreasing gestation a trend for prolonged PoM was found (p<0.001). The mean (SD) PoM duration was prolonged in group A: 7.8 days (2.5); group B: 4.3 days (2.4); and group C: 2.9 days (1.3) compared to term infants. Furthermore, PoM was associated with birth weights ⩽2500 g (p = 0.03) and morphine therapy (p = 0.03). Duration of PoM was not associated with type of feeding, small for gestational age, large for gestational age or need for respiratory support. Conclusion: PoM was not only delayed but also prolonged in preterm infants. Duration of PoM was associated with GA, birth weight and morphine therapy.